Improvement in early diagnosis of Japanese spotted fever by using a novel Rick PCR system. Issue 11 (1st July 2015) - Kondo, Makoto; Akachi, Shigehiro; Kawano, Mitsuo; Yamanaka, Keiichi; Yamagiwa, Akisa; Gabazza, Esteban C.; Ando, Katsuhiko; Mizutani, Hitoshi
Abstract Rickettsia diseases, including Japanese spotted fever (JSF), are serious infections. Delayed diagnosis occasionally results in life‐threatening liver disorders and disseminated intravascular coagulation (DIC). Because of the shortness of the latent period, serological diagnosis is not preferable for early diagnosis of JSF. Until now, a polymerase chain reaction (PCR)‐based diagnosis method has been used for early diagnosis, and the sensitivity reaches as high as 90% using skin biopsy samples as we previously reported. On the other hand, the sensitivity of the same PCR method using blood samples is limited at less than 50%. In the present study, using peripheral blood samples, we developed a novel diagnostic method for JSF using a Rick PCR system with original PCR primers, showing improved sensitivity compared with the conventional nested PCR. It may constitute a preferable diagnostic tool for early and sensitive diagnosis of Rickettsia infection.